Proximate and amino acid composition of quail meat treated with mega floral booster addition - Sharif, U.H.; Kamarudin, A.S.; Huda, N. (2018)
This study evaluated the effect of Mega Floral Booster (MFB) as probiotic supplement on the quality properties such as the carcass yield, physicochemical properties and nutritional composition of quail meat. Mega flora booster is the multi-probiotic animal feed additive. The treatment is divided to four treatments based on percentage of MFB include MFB-0.00 (control), MFB-0.05 (0.05% of MFB), MFB-0.20 (0.20% of MFB) and MFB-0.35 (0.35% of MFB). The 18 of quail species Cortunix japonica (Japanese quail) used as the main material in the study for each treatment. For the first until fourteen days, the quails are supplied with commercial feed only. After fifteen days, the quails begin provided with the MFB-0.00, MFB-0.05, MFB-0.20 and MFB-0.35 mixed with commercial feed. The quails for 42 days slaughtered and deboned of breast and whole leg separated from the bone for analysis. Probiotic supplement (Mega Floral Booster) had no influence on proximate and amino acid composition. Chemical score and amino acid score was show tryptophan as amino acid limited. Essential Amino Acid index of breast meats presented MFB-0.20 (61.66%) higher than MFB-0.00 (60.26%). Thus, Mega Floral Booster is not affecting the nutritional quality of quail meats.